The Effect of English Podcast on ESL Students Listening Comprehension Skills - Asasi Syifa; Yeni Mardiyana; Widya Oktarini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to evaluate the effect of using English podcasts on the listening comprehension skills of ESL (English as a Second Language) students using a pre-experimental one-group pretest post-test design. The sample consisted of 35 ESL students. The students were given a listening comprehension test before the intervention (pretest) to measure their initial skills. During a four-week period, the students were regularly exposed to English podcasts selected based on difficulty level and relevance to the curriculum. After the intervention period, the same listening comprehension test was administered as a post-test to measure changes in listening skills. The collected data were analyzed using a paired t-test to determine the significance of the difference between pretest and post-test scores. The results showed a significant increase in students' listening comprehension scores after the podcast intervention (p < 0.05). These findings indicate that regular use of English podcasts can improve ESL students' listening comprehension skills. This study suggests that podcasts can be an effective tool in language learning, particularly in enhancing listening skills. The practical implication of this research is to encourage educators to integrate podcasts into their teaching methods. Further research is recommended to address the limitations of this study design and explore other factors that may influence the results.